GAMMA DOSE RATES IN THE HIGH BACKGROUND RADIATION AREA OF MANGALORE REGION, INDIA. Issue 3 (12th July 2019) - Al-Azmi, Darwish; Kumara, Sudeep; Mohan, M P; Karunakara, N
Abstract: Elevated levels of natural background radiation due to scattered patches of monazite sand around the beaches of Mangalore, India, have been reported earlier. A comparative study of gamma dose rates was performed in both normal background and high natural background radiation areas around Mangalore using different types of portable gamma dosimeters. In addition to this, gamma-ray energy spectra were acquired, in situ, using a NaI(Tl) based portable gamma spectrometer. Soil and sand samples were collected for laboratory analysis with HPGe detectors. Measurements were carried out during the years 2016–18 revealed that in majority of the locations the gamma dose rates were similar to the normal background regions, whereas, in certain locations the dose rates were higher with values up to 530 nSv/h.